How the Emerging Balkan-Israeli Strategic Alliance could Alter Energy Security in the Eastern Mediterranean Basin - Neubauer, Sigurd (Journal of Regional Security, 2018)
This paper seeks to analyze Israel’s emerging strategic alliance with the Balkan countries, not only as an “alternative” to Turkey, but rather expose how interest-driven policies are rapidly shaping deepening political, military & intelligence cooperation with Cyprus, Greece, Romania and Bulgaria. At the backdrop of Israel’s quest to form alternative alliances with non-Middle Eastern states close to its geographical vicinity, is its apparent interests in exporting newly discovered energy riches to European markets. Aside from commercial aspects driving Israel’s relations with Greece and Cyprus, it remains unclear how viable a Balkan-Israel alliance can be without some sort of Turkish-Israeli rapprochement.